Strength Enhancement Study on Composites of AA6066 Aluminium Alloy with Magnesium Oxide and Coal Ash. (13th July 2021) - Ponraj Sankar, L.; Aruna, G.; Sathish, T.; Parthiban, A.; Vijayan, V.; Dinesh Kumar, S.; Rajkumar, S.; Mekonnen, Addisalem; Tufa, Mebratu
Abstract : Aluminium alloy is the most favourable material based on the various properties and economic factors. Always there are so many researches going on based on the enhancement of the material properties with various combinations and the various materials mixing rate depending upon the availability. These researches were focused on the augmentations of the properties, and then the corresponding properties can be used in the various applications depending upon the results. In this study, the AA6066 aluminium alloy composites were created with the magnesium oxide and coal ash with a variety of grouping. The specimens were named as AAMgOCA 1 to AAMgOCA 6 with respect to the volume concentration composition. Then, the composites were tested to identify the impact on various strengths such as yield strength, ultimate tensile strength, shear strength, and flexural strength. These strengths were compared with the two conditions of the composites such as annealed and heat-treated conditions. AAMgOCA 3 has the greatest results in heat-treated condition when compared with the annealed condition.